Economic reforms and its impact on poverty of India - Usha, S. (2006)
This paper studies the impact of Economic reforms on poverty in the economy. Ensuring the minimum standards for various social services and amenities are deemed to be the responsibility of the state. These concepts are related with various developmental policies and economic reforms adopted by the government. - Reproduced.
Keywords: Poverty - India; Economic reform - India; Economic reform